Environmentally Responsive Hydrogels and Composites Containing Hydrogels as Water-Based Lubricants - Song Chen; Zumin Wu; Lei Wei; Xiuqin Bai; Chengqing Yuan; Zhiwei Guo; Ying Yang (Gels, 2025)
Both biosystems and engineering fields demand advanced friction-reducing and lubricating materials. Due to their hydrophilicity and tissue-mimicking properties, hydrogels are ideal candidates for use as lubricants in water-based environments. They are particularly well-suited for applications involving biocompatibility or interactions with intelligent devices such as soft robots. However, external environments, whether within the human body or in engineering applications, often present a wide range of dynamic conditions, including variations in shear stress, temperature, light, pH, and electric fields. Additionally, hydrogels inherently possess low mechanical strength, and their dimensional stability can be compromised by changes during hydration. This review focuses on recent advancements in using environmentally responsive hydrogels as lubricants. It explores strategies involving physical or structural modifications, as well as the incorporation of smart chemical functional groups into hydrogel polymer chains, which enable diverse responsive mechanisms. Drawing on both the existing literature and our own research, we also examine how composite friction materials where hydrogels serve as water-based lubricants offer promising solutions for demanding engineering environments, such as bearing systems in marine vessels.